Reproductive life history of the introduced peacock grouper Cephalopholis argus in Hawaii. Issue 2 (26th June 2016) - Schemmel, E. M.; Donovan, M. K.; Wiggins, C.; Anzivino, M.; Friedlander, A. M.
Abstract : This research investigated the reproductive biology (sex ratio, hermaphroditic pattern, size and age at maturity) of Cephalopholis argus, known locally in Hawaii by its Tahitian name roi. The results suggest that C. argus exhibits monandric protogyny (female gonad differentiation with female to male sex change) with females reaching sexual maturity at 1.2 years (95%c.i .: 0.6, 1.6) and 20.0 cm total length ( L T ; 95%c.i .: 19.6, 21.2). The female to male sex ratio was 3.9:1. The average age and L T at sex change was 11.5 years (95%c.i .: 11.1, 12.9) and 39.9 cm (95%c.i .: 39.5, 41.2), respectively. Current information on spawning seasonality of this species is incomplete, but based on the occurrence of spawning capable and actively spawning females, spawning probably takes place from May to October. Evidence of lunar spawning periodicity was found, with an increased proportion of spawning capable and actively spawning females, and an increased female gonado‐somatic index during first quarter and full‐moon phases. This information fills a valuable information gap in Hawaii and across the species' native range.